If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 3x = -18 + 8x Solving -3 + 3x = -18 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -3 + 3x + -8x = -18 + 8x + -8x Combine like terms: 3x + -8x = -5x -3 + -5x = -18 + 8x + -8x Combine like terms: 8x + -8x = 0 -3 + -5x = -18 + 0 -3 + -5x = -18 Add '3' to each side of the equation. -3 + 3 + -5x = -18 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = -18 + 3 -5x = -18 + 3 Combine like terms: -18 + 3 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| 41z-9=41z-9 | | 645/18-603/4 | | n*40=13 | | -7w-7=-15-15w | | 7x-1=-29 | | 9+4x=-5x-2 | | y=7/5x-7 | | 4(x+4)=2(x+5)+6 | | .08x+.11(3x+38000)=34110 | | 1290*3x+49(5x)=1 | | 1290*3x+49(5x)=17093 | | 1290*3x+49(5x)=17 | | 2+y=0.3v-8 | | =0.3v-8 | | .04x+.07(5000-x)=300 | | 15(2x-1)=5(x+2)+2 | | f(x)=-3x^2+5 | | 10w+4=8-4w | | 9+2x=2x-6 | | 4/3(x-72) | | y+2=0.3*v-8 | | 5-2(0)=0 | | 3/4(x-9)=4/5(5x-7) | | y+2=0.3v-8 | | 15x^2+26+8=0 | | (x+2y)dx-xdy=0 | | x(x-4)=2 | | -10z-2=-z+7 | | r^2+24r+169=0 | | 2p^2=-18p | | 4d^2+15d-4= | | 5+8(x-2)=(3x+1)4+1 |